Application of n-of-1 Clinical Trials in Personalized Nutrition Research: A Trial Protocol for Westlake N-of-1 Trials for Macronutrient Intake (WE-MACNUTR). Issue 9 (26th August 2020) - Tian, Yunyi; Ma, Yue; Fu, Yuanqing; Zheng, Ju-Sheng
ABSTRACT: Personalized dietary recommendations can help with more effective disease prevention. This study aims to investigate the individual postprandial glucose response to diets with diverse macronutrient proportions at both the individual level and population level, and explore the potential of the novel single-patient ( n -of-1) trial for personalization of diet. Secondary outcomes include individual phenotypic responses and the effects of dietary ingredients on the composition of gut microbiota. Westlake N-of-1 Trials for Macronutrient Intake is a multiple crossover feeding trial consisting of 3 successive 12-d dietary intervention pairs including a 6-d washout period before each 6-d isocaloric dietary intervention: a 6-d high-fat, low-carbohydrate diet, and a 6-d low-fat, high-carbohydrate diet. The results will help provide personalized dietary recommendations for macronutrients in terms of postprandial blood glucose responses. The proposed n -of-1 trial methods could help in optimizing individual health and advancing health care. This trial was registered with clinicaltrials.gov (NCT04125602). Abstract : WE-MACNUTR addresses the individual postprandial glucose response to two isocaloric dietary interventions and evaluates the utility of n-of-1 approach in the personalization of dietary recommendation.